Writing after the End. Towards an anthropology of post-apocalyptic Bildungroman (ENTHYMEMA, 2023)
In La terra dei figli (2016) Gipi implicitly proposes, between the lines of a post-apocalyptic tale, a critical reflection on writing, on the uses and risks of this communicative resource and on itsrelevance as a fundamental cultural pillar of our civilization. The contribution investigates this theme by activating the hermeneutic potential of a classic such as Ernesto De Martino’s study on cultural apocalypses and methodologically situating Gipi’s work within the current production of postapocalyptic narratives, and among them, in particular, those having young adults or adolescents as protagonists. Associated as a whole in the hybrid genre of post-apocalyptic Bildungroman, these narratives are interpreted as a symbolic form of post-modernity, according to Franco Moretti’s theoretical-methodological model. What emerges in conclusion is the attitude of a reassuring reproposition of the cultural values of contemporary civilization, albeit in the context of apocalyptic imagery, potentially rich in critical and polemical implications.
Keywords: Writing; Graphic novel; Bildungroman; Postapocalyptic narratives; Gipi (Gian Alfonso Pacinotti)